2017
DOI: 10.1177/1063426617739638
|View full text |Cite
|
Sign up to set email alerts
|

Teacher Reports of Verbal Aggression in School Settings Among Students With Emotional and Behavioral Disorders

Abstract: Aggression among children and adolescents can be a highly stable behavior and serves as a significant predictor for later aggression and a variety of other undesirable outcomes for both the aggressor and victim including, but not limited to, low self-worth, poor academic performance, and hopelessness (Hanley & Gibb, 2011; Rueger & Jenkins, 2014). Aggression by students against peers and adults in school environments is not just an issue about instances of injury by physical force but also include acts of aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
43
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(49 citation statements)
references
References 55 publications
4
43
2
Order By: Relevance
“…Specifically, these researchers found that among students with EBD, 71% of the teachers reported daily observance of student-to-student VA and 57.3% indicated daily student-to-adult VA. In the same study, Taylor and Smith (2019) found that 64% of the teachers who served students with EBD reported that their students were more verbally aggressive than their typical peers and that their students responded to acts of VA primarily with retaliatory acts of verbal or physical aggression. Moreover, these researchers found that a majority of teachers described students frequently reporting, complaining, or seeking advice about issues related to VA, and they reported that VA takes place in multiple locations, with at least one bystander present, and they observed victim verbal retaliation and physical assaults because of VA. Interestingly, Taylor and Smith (2019) found that teacher responses included redirection and verbal warnings, and few teachers reported instruction of alternative prosocial behaviors.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…Specifically, these researchers found that among students with EBD, 71% of the teachers reported daily observance of student-to-student VA and 57.3% indicated daily student-to-adult VA. In the same study, Taylor and Smith (2019) found that 64% of the teachers who served students with EBD reported that their students were more verbally aggressive than their typical peers and that their students responded to acts of VA primarily with retaliatory acts of verbal or physical aggression. Moreover, these researchers found that a majority of teachers described students frequently reporting, complaining, or seeking advice about issues related to VA, and they reported that VA takes place in multiple locations, with at least one bystander present, and they observed victim verbal retaliation and physical assaults because of VA. Interestingly, Taylor and Smith (2019) found that teacher responses included redirection and verbal warnings, and few teachers reported instruction of alternative prosocial behaviors.…”
mentioning
confidence: 89%
“…Numerous sources estimate that between 2% and 7% of the school population in the United States exhibit significant, long-term emotional or behavioral problems that often involve strong negative emotions and aggression that interfere with academic and social learning (Forness, Kim, & Walker, 2012; Kauffman & Landrum, 2017). Students who receive special education (SE) services for emotional and behavioral disorders (EBD) often display high rates of externalizing (e.g., chronic noncompliance, verbal and physical aggression) and internalizing (e.g., anxiety and depression) behavior problems and they constitute a significant percentage of students isolated from the mainstream of education (Kauffman & Landrum, 2017; Office of Special Education and Rehabilitative Services, Office of Special Education Programs, 2017; Taylor & Smith, 2019). According to C.…”
mentioning
confidence: 99%
See 3 more Smart Citations